2010
DOI: 10.1007/s13197-010-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of idli batter, its properties and nutritional improvement during fermentation

Abstract: Idli is a traditional fermented rice and black gram based food. Idli batter is prepared by soaking polished parboiled rice and decorticated black gram for 4 h at 30±1°C in water. The soaked mass was ground using a grinder with adequate amount of water. The blend ratios of 2:1, 3:1 and 4:1 (w/w) batter were allowed for fermentation for different periods with the addition of 2% (w/w) of salt. The rheology of the product was assessed using a Brookfield Viscometer having disc spindles. Shear stress values were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…These findings are in accordance with the data reported by Rekha and Vijayalakshmi (2011) where at the end of 10 h natural fermentation at 30°C there was a 20 % increase in volume in the unfortified idli batter and a 55 % increase in volume in okara fortified batter. Ghosh and Chattopadhyay (2011) reported that increase in blend ratio significantly increased the batter density. Balasubramanian and Viswanathan (2007) reported similar bulk density between 0.94 and 0.59 g cm -3 in idli batter with different ratios of rice and black gram [2:1, 3:1 and 4:1 (v/v)].…”
Section: Bulk Density and Viscositymentioning
confidence: 98%
“…These findings are in accordance with the data reported by Rekha and Vijayalakshmi (2011) where at the end of 10 h natural fermentation at 30°C there was a 20 % increase in volume in the unfortified idli batter and a 55 % increase in volume in okara fortified batter. Ghosh and Chattopadhyay (2011) reported that increase in blend ratio significantly increased the batter density. Balasubramanian and Viswanathan (2007) reported similar bulk density between 0.94 and 0.59 g cm -3 in idli batter with different ratios of rice and black gram [2:1, 3:1 and 4:1 (v/v)].…”
Section: Bulk Density and Viscositymentioning
confidence: 98%
“…Spindle #6 was used for all measurements. Since the viscometer did not give direct shear rate and shear stress values for disc-type spindles, shear rate and shear stress values were obtained from the torque-rpm readings by calculation following the procedure described by Mitschka (1982) and Gbosh and Chattopadhyay (2010). The procedure involves taking measurements of many pairs of torques (α i ) with a spindle for fixed values of viscometer speed N i (rpm).…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…It is preferred by many people around the world because of its spongy texture, appearance, mouth feel, taste and aroma (Iyer and Ananthanarayan, 2008). The ingredients of idli are milled rice (Oryza sativa) and dehulled black gram (Phaseolus mungo) (Ghosh and Chattopadhyay, 2011). Rice and black gram are soaked separately and ground in a mortar and pestle with adequate water to yield a coarse rice batter and fine black gram batter (Blandino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%